Electrocardiography of arrhythmias : a comprehensive review - Das, Mithilesh K.; Zipes, Douglas P. (Elsevier/Saunders, 2012)
Equips you with the knowledge and clinical competencies you need to accurately interpret electrocardiograms (ECG) and ace the ECG part of cardiology boards or the ABIM ICE ECG certifying exam. This title offers a review of electrocardiography.